Etomidate anaesthesia by immersion in oriental fire-bellied toads (Bombina orientalis). (October 2015) - d'Ovidio, D; Spadavecchia, C; Angeli, G; Adami, C
The objective of the present study was to evaluate the efficacy and the safety of etomidate anaesthesia by immersion technique in Bombina orientalis . The study comprised two phases. The first phase was carried out to identify the etomidate concentration capable of producing anaesthetic induction, as well as surgical anaesthesia, in the toads. The second phase was aimed at testing that concentration in eight additional animals. Etomidate administered via immersion at a concentration of 37.5 mg/L produced effective anaesthesia in oriental fire-bellied toads. The average duration of surgical anaesthesia was 20 min. All the toads enrolled in the study survived the anaesthesia and long-term complications did not occur. However, undesired side-effects, namely itching, myoclonus and prolonged recovery, were noticed during the perianaesthetic period. The authors concluded that etomidate anaesthesia by immersion, at a concentration of 37.5 mg/L, is suitable in oriental fire-bellied toads and produces anaesthesia of a depth and duration that is sufficient to allow the completion of various experimental procedures, without resulting in lethal complications. However, the occurrence of undesired side-effects opens a debate on the safety of this anaesthetic technique, and imposes the need for further investigation prior to proposing the latter for routine laboratory practice.